Membedah Diskursus dan Berkreasi dalam Ranah Pluralitas: Rereading Arkeologi Pengetahuan - Sanusi, Irfan (Jurnal Ilmu Dakwah, 2010)
Archaeology tries to define not the thoughts, representations, images, themes, preoccupations that are concealed or revealed in discourses; but those discourses themselves, those discourses as practices obeying certain rules. (Michel Foucault)Archaeology tries to define not the thoughts, representations, images, themes, preoccupations that are concealed or revealed in discourses; but those discourses themselves, those discourses as practices obeying certain rules. (Michel Foucault)